Do Not Think Carefully? Re-examining the Effect of Unconscious Thought on Deception Detection - Wu, Song; Mei, Hongyu; Yan, Jiali (Frontiers in Psychology, 2019)
Several recent studies have examined the effect of unconscious thinking on deception detection with the hypothesis that unconscious thought increases the ability to discriminate between truth and deception, but these studies yielded conflicting results. The present study aimed to re-examine the effect of unconscious thinking and extend it by adopting both verbal and nonverbal/paraverbal materials. We hypothesized that unconscious thought leads to a higher accuracy rate than immediate decision and conscious thought when judging nonverbal/paraverbal materials, but not when judging verbal materials. In Study 1, we compared unconscious thought with immediate decision by using both video and audio materials. In Study 2, we compared unconscious thought with conscious thought by using both video and text materials. The results showed that when detecting deception versus truth, (1) unconscious thought was not better than immediate decision on deception detection in both audio and video conditions (Study 1), and (2) unconscious thought was not better than conscious thought in both video and text conditions (Study 2). The Bayes factor of both studies also showed substantial evidence for null hypothesis (H0) relative to alternative hypothesis (H1). The implications and limitations of the present study are discussed.